Kinematic analyses of Parkour landings from as high as 2.7 meters - Dai, B.; Layer, J. S.; Hinshaw, T. J.; Cook, R. F.; Dufek, J. S. (Journal of Human Kinetics, 2020)
Developing effective landing strategies has implications for both injury prevention and performance training. The purpose was to quantify the kinematics of Parkour practitioners` landings from three heights utilizing four techniques. Seventeen male and three female Parkour practitioners landed from 0.9, 1.8, and 2.7 m utilizing the squat, forward, roll, and stiff landing techniques when three-dimensional kinematics were collected. The stiff landing demonstrated the shortest landing time, and the roll landing showed the longest landing time for 1.8 and 2.7 m. Roll landings demonstrated the greatest forward velocities at initial contact and at the end of the landing. Stiff landings showed the greatest changes in vertical velocity during the early landing, while roll landings showed the least changes for 0.9 and 1.8 m. Both roll and stiff landings generally resulted in decreased changes in horizontal velocity during the early landing compared to squat and forward landings. The four landing techniques also demonstrated different lower extremity joint angles. Stiff landings may increase injury risk because of the quick decrease of vertical velocities. Roll landings allow individuals to decrease vertical and horizontal velocities over a longer time, which is likely to decrease the peak loading imposed on the lower extremities.